ANALISIS IMPLEMENTASI PROGRAM PERLINDUNGAN ANAK TERPADU BERBASIS MASYARAKAT (PATBM) DALAM PENANGANAN KASUS KEKERASAN TERHADAP ANAK DI KABUPATEN SUMBAWA BARAT - AYU DEWI HASTUTY; UMAR UMAR; MIETRA ANGGARA (Universitas Mahasaraswati K. Mataram, 2023)
This research discusses the analysis of the implementation of the Community-Based Integrated Child Protection Program (PATBM) in handling cases of violence against children in West Sumbawa Regency. The aims of this research are; 1) To find out the implementation of the PATBM program in handling violence against children in West Sumbawa Regency. 2) To analyze community perceptions of the implementation of the PATBM program in handling cases of violence against children in West Sumbawa Regency. This research uses a qualitative descriptive approach because researchers want to find facts related to the effectiveness of implementing PATBM in the context of monitoring and evaluation at the West Sumbawa Regency Family Planning, Women's Empowerment and Child Control (DP2KBP3A) Population Control Service. The research informants involved were 25 respondents. These respondents were divided into two groups, namely: the first group, Head of Service, Head of Division, 2 Kasie, and 1 head of UPTD PPA West Sumbawa Regency with a total of 5 respondents, the second group, representing the community victims of violence in West Sumbawa Regency. The research results showed that the implementation of the Community-Based Integrated Child Protection Program (PATBM) in West Sumbawa Regency reflects a very relevant approach in handling cases of violence against children. Community perception of the implementation of the Community-Based Integrated Child Protection Program (PATBM) in handling violence against children in West Sumbawa Regency is very important in evaluating the effectiveness of this program. The implementation of the PATBM program in handling violence against children in West Sumbawa Regency has had a significant positive impact in protecting children from various forms of violence